Health-Related Quality of Life and Gender Differences in Elderly People: a Cross-Sectional Study - Pegah Bahrami Taghanaki; Ehsan Mosa Farkhani; Sima Nourbakhsh; Maryam Srakhosh (Elderly Health Journal)
Introduction: As the population is aging, concerns are raised regarding the quality of life of elderly people. Men and women tend to experience aging differently due to socioeconomic differences. Therefore, this study aims to investigate the state of health-related quality of life and its gender-related discrepancies in the elderly population in Mashhad, Iran. Methods: This cross-sectional study was conducted on 200 elderly population in Mashhad, Iran. Following a multi-staged stratified sampling, participants were selected, and in order to complete the questionaries interviewed at their homes or the Health Center according to the participants’ priorities using the RAND 36-Item Health Survey (RAND-36). The survey consists of 8 scales of physical functioning (PF), role limitations caused by physical health problems (RP), role limitations caused by emotional problems (RE), social functioning (SF), emotional well-being (EW), energy/fatigue (EF), pain (P), and general health (GH). Data were analyzed using Chi-Square test. Results: Men exhibited significantly higher scores on PF (71.38 ( ± 24.13) vs 57.63 ( ± 24.75), p =0.00), SF (74.22 ( ± 17.99) vs 67.27 ( ± 18.61), p =0.01), and p (77.38 ( ± 23.76) vs 64.79 ( ± 27.77), p =0.00) dimensions compared to women. Post-hoc analyses revealed that the main factors influencing the differences were variations between ages (60-65) with (70-75) and over 80 regarding PF, ages (60-65) with over 80 in RP, and finally, the difference attributed to ages (60-65) with (65-70) in GH. The comparison between the states of employment revealed that the employed individuals ranked higher in all dimensions except pain. Conclusion: This study provides an overall description of the state of the health-related quality of life of the elderly in Mashhad underscoring the differences that genders exhibit in each dimension which calls for a broader gender-based assessment of quality of life in this population in Mashhad and Iran.